ATTEMPTED SUICIDE IN LUDHIANA - Narang, R.L. (Medknow Publications, 2000)
This study assesses the various socio-demographic correlates, the method adopted and the psychiatric disorders in patients with attempted suicide. Out of 208 cases presented to the hospital, one hundred individuals with suicide attempt were included in the present study. They were evaluated for socio-demographic profile and psychiatric illness on the basis of ICD-10 criteria. Analysis of the results showed that single males outnumbered single females, whereas married females outnumbered married males in suicidal attempt. The prevalence of suicidal attempt was high among males with psychiatric illness, whereas more female suicide attempters were without psychiatric illness. The most common psychiatric illnesses were found to be mood disorders (35%) and adjustment disorders (13%) as per the ICD-10 criteria. Family type, economic status and education levels appears to be playing non significant role in suicide attempt in this part of the country Marital status and psychiatric illnesses are playing important role in suicide attempt. Other demographic variables, though, were statistically non significant, but, below 30 years of age group, low socio-economic status, low education and nuclear families were found to be more vulnerable factors for suicide.